2013
DOI: 10.1590/s1516-89132013005000008
|View full text |Cite
|
Sign up to set email alerts
|

Production of grape juice powder obtained by freeze-drying after concentration by reverse osmosis

Abstract: This study aimed to evaluate the freeze-drying process for obtaining grape juice powder by reverse osmosis using 50% grape juice

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 21 publications
(29 reference statements)
5
11
0
2
Order By: Relevance
“…The water activity (a w ) of all microencapsulated products ( Figure 1 B) was ranged from 0.310 to 0.450, and all final encapsulated products were noticeably dissimilar from one another, apart from T B (5% GA & 5% MD). T D (10% MD) demonstrated the maximum a w value of 0.450 which was corroborating with previous study carried out by Gurak et al [ 42 ] who found that a w of grape fruit drink microencapsulated by the means of maltodextrin utilizing lyophilization technique was 0.430.…”
Section: Resultssupporting
confidence: 90%
“…The water activity (a w ) of all microencapsulated products ( Figure 1 B) was ranged from 0.310 to 0.450, and all final encapsulated products were noticeably dissimilar from one another, apart from T B (5% GA & 5% MD). T D (10% MD) demonstrated the maximum a w value of 0.450 which was corroborating with previous study carried out by Gurak et al [ 42 ] who found that a w of grape fruit drink microencapsulated by the means of maltodextrin utilizing lyophilization technique was 0.430.…”
Section: Resultssupporting
confidence: 90%
“…The MPs (Fig. 2a-c) showed smooth surfaces and irregular, flake-like structures of different sizes, eventually forming aggregates, which was expected because the powders were freeze-dried and ground in mortar (Gurak et al 2013). Figure 2b shows that MD was the encapsulating agent that enabled the formation of capsules with fewer wrinkles on their surfaces, which is in accord with the research of Silva et al (2014).…”
Section: Surface Characteristics Powders and Filmsupporting
confidence: 77%
“…The water activity (aw) of all microencapsulated products ( Figure 1B) was ranged from 0.310 to 0.450, and all final encapsulated products were noticeably dissimilar from one another, apart from TB (5% GA and 5%MD). TD (10% MD) demonstrated the maximum aw value of 0.450 which was corroborating with previous study carried out by Gurak et al [52] who found that aw of grape fruit drink microencapsulated by the means of maltodextrin (MD) utilizing lyophilization technique was 0.430.…”
Section: Physical Characteristics Of Microencapsulated Powder Productssupporting
confidence: 91%